The efficacy of hepatic protectors in patients having chronic hepatitis - E. I. Beloborodova; A. I. Vengerovsky; I. K. Livshits; Ye. V. Beloborodova; V. A. Burkovskaya; D. I. Kuzmenko (Бюллетень сибирской медицины, 2008)
The purpose of the present work was the study of new hepatic protectors liproksol influence in the chronic hepatitis viral and alcohol etiology in comparison of carsil effect. 69 patients having chronic hepatitis were include in the investigation. The patients were divide on two group. Group I (35 patients) received liproksol monotherapy. Group II (34 patients) received carsil monotherapy. The course of treatment composed 28—30 days. The investigation revealed that liproksol has hepatoprotective activity comparable carsil activity. There was no side effect of liproksol.